A motor neuron protective role of miR-969 mediated by the transcription factor kay. Issue 9 (1st September 2020) - Zhang, Xiao; Lyu, Jialan; Jin, Xiaoye; Yang, Weiwei; Lou, Ziwei; Xi, Yongmei; Yang, Xiaohang; Ge, Wanzhong
ABSTRACT: Maintenance of motor neuron structure and function is crucial in development and motor behaviour. However, the genetic regulatory mechanism of motor neuron function remains less well understood. In the present study, we identify a novel neuroprotective role of the microRNA miR-969 in Drosophila motor neurons. miR-969 is highly expressed in motor neurons. Loss of miR-969 results in early-onset and age-progressive locomotion impairment. Flies lacking miR-969 also exhibit shortened lifespan. Moreover, miR-969 is required in motor neurons. We further identify kay as a functionally important target of miR-969. Together, our results indicate that miR-969 can protect motor neuron function by limiting kay activity in Drosophila .